Influence of powder loading on rheology and injection molding of Fe-50Ni feedstocks - Ali, M. (Taylor and Francis Inc., 2020)
The feedstock viscosity is a crucial rheological parameter that governs the failure or success of injection molding, whereas viscosity depends upon powder morphology and process parameters. Thus, rheological investigation of the feedstock is essential to find out the optimum loading and suitable processing parameters to produce high-quality defect-free green parts by injection molding. The critical powder volume percentage (CPVP) was determined for both Fe and Ni powders produced by carbonyl and atomization routes. The CPVP value for carbonyl powders was 56.47 vol while for atomized powders was 60.49 vol. The higher value for atomized powder was due to regular morphology as compare to spiky irregular shape carbonyl Ni particles. Three feedstocks of carbonyl powders from 52 to 56 vol loading and three of atomized with loading from 56 to 60 vol were prepared. The optimum loading was established in terms of activation energy, viscosity, and flow behavior index at three temperatures. The formulations of 54 vol loading and 58 vol loading for carbonyl and atomized powders, respectively, were found appropriate for injection molding. Â© 2020, Â© 2020 Taylor & Francis.